The Effect of Javelin Modification on Javelin Throwing Results in Elementary School Students - Ahmad Yani; Mudayat Mudayat (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The aim of this study is to investigate the impact of javelin training on the throwing performance of fifth-grade pupils in the javelin throwing category at Kuranji Elementary School, Serang City. The study will compare the findings of pretest and posttest measurements. Materials and Methods. The study consisted of a group of 27 fifth grade pupils. The sample method employed was non-probability sampling, specifically utilizing a saturated sampling methodology which involved including all members of the population. The data were collected using test and measurement methodologies. The research strategy employed was the One-Group Pretest-posttest strategy. The research methodology employed in this study was the pre-experimental experimental approach. The tool utilized in this research was the javelin throwing test, employing modified javelin media. Result. The study presents the outcomes of the pretest to posttest analysis on the impact of javelin training in the athletics branch, specifically in the javelin throwing event, for grade V students of Kuranji Elementary School in Serang City. The calculation yielded a t-count value of 7.430, which was then translated to a t-count value with a significance level of 0.05. The degrees of freedom (n-1) was 26, resulting in a value of 1.706. The t-count number is more than the t-table value of 2.023, indicating statistical significance. The therapy has a significant influence of 37.01%, while the remaining 62.99% is attributed to other factors that have not been investigated. Conclusion. The study revealed a notable rise in javelin throwing performance, as indicated by the scores obtained in the pre-test and post-test, when utilizing bamboo training.